Anomalous behavior of Hc3/Hc2 near Tc for Sn-In and In-Bi alloys systems. - Maloney, M. D.; de la Cruz, F.; Cardona, M. (Departament of Physics of Brown University., 1970)
Fil: Maloney, M. D. Comisión Nacional de Energía Atómica; Argentina